Improving Teachers' Ability to Write New Prose (Short Stories) in Making Higher Order Thinking Skill (HOTS) Questions through In House Training at SD Negeri Banjarsari, Samigaluh, Kulon Progo Regency for 2021/2022 Academic Year - Sutiyatmi (Universitas Islam Indonesia, 2023)
This study aims to determine the teacher's ability to write new prose short stories on making higher-order thinking Skills HOTS through in-house Training (IHT). This type of research is School Action Research (PTS) with a qualitative descriptive method conducted for two cycles. The sample in this study was 6 teachers at SD Negeri Banjarsari Samigaluh, Kulon Progo Regency. Data collection techniques in this study through observation and documentation. The results of the study showed an increase in the teacher's ability to write new prose, where in cycle I at the first meeting an average score of 68.33 was obtained; and in cycle II at the second meeting, an average value of 92.22 was obtained. In writing HOTS questions by including new prose for cycle I at the first meeting an average value of 81.11 was obtained, while in cycle II for the second meeting, an average value was obtained of 86.22. In the implementation of IHT participants conducted an assessment of the resource person, where in the first cycle for the first meeting an average value of 78 was obtained in the